Islamic Religious Education at Pre-Baligh Age According to Ibn Qayyim Al Jauziy - Euis Sufi Jatiningsih; Imas Kania Rahman; Hendri Tanjung (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This article discusses the subject matter of curriculum for pre-baligh children's education in terms of the thoughts of Ibn Qayyim Al Jauzi and is enriched with other thoughts that refer to Al- Qur'an and hadith. This study uses the library research method, especially in the book Tuhfah Al-Maudud bil Ahkamil Maulud, written by Ibn Qayyim Al-Jauzy. The results of the study show that Imam Ibn Qayyim Al-Jauzi is very detailed in detailing what material or curriculum should be given to children, even from 0 to 2 years old. It was also found that the choice of the word